2015
DOI: 10.1104/pp.15.00110
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Arabidopsis and Wheat to Rising CO2 Depend on Nitrogen Source and Nighttime CO2 Levels

Abstract: A major contributor to the global carbon cycle is plant respiration. Elevated atmospheric CO 2 concentrations may either accelerate or decelerate plant respiration for reasons that have been uncertain. We recently established that elevated CO 2 during the daytime decreases plant mitochondrial respiration in the light and protein concentration because CO 2 slows the daytime conversion of nitrate (NO 3 2 ) into protein. This derives in part from the inhibitory effect of CO 2 on photorespiration and the dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 50 publications
2
41
2
Order By: Relevance
“…In addition, elevated CO 2 during the daytime reduced mitochondrial respiration in the light and total protein amount because CO 2 decreased the daytime conversion of NO 3 -into proteins (Rubio-Asensio et al 2015). These studies clearly reflect enhanced central carbon metabolites in A. thaliana in response to elevated CO 2 .…”
Section: A Thalianamentioning
confidence: 95%
“…In addition, elevated CO 2 during the daytime reduced mitochondrial respiration in the light and total protein amount because CO 2 decreased the daytime conversion of NO 3 -into proteins (Rubio-Asensio et al 2015). These studies clearly reflect enhanced central carbon metabolites in A. thaliana in response to elevated CO 2 .…”
Section: A Thalianamentioning
confidence: 95%
“…() suggested that eCO 2 may reduce the strength of the plant N sink and thus constrain plant N utilization. Other studies have shown that eCO 2 reduced nitrate (NO3) assimilation in C3 plants (Asensio, Rachmilevitch, & Bloom, ; Bloom, Burger, Rubio‐Asensio, & Cousins, ; Bloom, Smart, Nguyen, & Searles, ) which could leave more NO3 substrate available for denitrification. In their meta‐analysis, van Groenigen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al (2015) suggested that eCO 2 may reduce the strength of the plant N sink and thus constrain plant N utilization. Other studies have shown that eCO 2 reduced nitrate (NO À 3 ) assimilation in C3 plants (Asensio, Rachmilevitch, & Bloom, 2015;Bloom, Burger, Rubio-Asensio, & Cousins, 2010;Bloom, Smart, Nguyen, & Searles, 2002) which could leave more NO À 3 substrate available for denitrification. In their meta-analysis, van Groenigen et al (2011) attributed increased N 2 O emissions under eCO 2 to enhanced denitrification resulting from both higher soil labile carbon (C) and soil moisture under eCO 2 .…”
mentioning
confidence: 99%
“…The linkages between nitrate assimilation and photorespiration have been recently described (Fan et al, 2016) using another approach: rice plants overexpressing the nitrate transporter NRT2.3b, which enhanced yield and N content, showed both reduced photorespiration and enhanced ammonium absorption. However, providing ammonium as the main N fertilization form has been described (Britto and Kronzucker, 2002) to be deleterious for plant performance and, independent of the [CO2], biomass production is reduced under NH4 + nutrition compared to NO3nutrition under elevated CO2 (Carlisle et al, 2012;Rubio-Asensio et al, 2015;Niu et al, 2013;Rubio-Asensio and Bloom, 2016). Within this context, our study aims to discuss the mechanisms that allow NR mutant plants to substantially overcome the inhibited phenotype associated with elevated [CO2].…”
Section: Discussionmentioning
confidence: 99%
“…It was predicted that N assimilation would also be impaired under elevated [CO2] because photorespiration is diminished by enhanced [CO2] and consequently ATP synthesis is decreased (Foyer et al, 2012). Furthermore, during the night period, NO3assimilation is also reduced in plants exposed to elevated [CO2] (Rubio-Asensio et al, 2015). Such an effect would be especially important in cases where plants are exclusively fertilized with NO3 -.…”
Section: Introductionmentioning
confidence: 99%